Motivations for Local Food Demand by Japanese Consumers: A Conjoint Analysis with Reference‐Point Effects. Issue 2 (5th October 2012) - Saito, Hisamitsu; Saito, Yoko
ABSTRACT Consumers often favor locally over nonlocally produced foods in the belief they have higher quality and provide the quasipublic service of conserving local agriculture. The aim of the present study is to clarify these two motivations' relative contributions to product demand by considering consumer reference points, that is preferences for remaining at present consumption and price levels. A stated‐preference method is applied to the Japanese demand for bread from local wheat. We find that Japanese consumers pay a significant premium for local wheat bread and that more than half the observed demand variation is explained by a product's quasipublic nature. In contrast, reference‐point effects suggest that those who frequently buy local food have a negative willingness‐to‐pay for imported or nonlocal‐domestic breads. Appealing to local food‐buyers' preferences for a local source and for environmental quality thus appears to be the most effective way of promoting local wheat bread. [JEL classifications: Q13; D12; D03].